Management Information System Pondok Pesanten Ma'hadut Tholabah Babakan Lebaksiu Tegal Regency - Adhi Santoso, Nugroho (Riviera Publishing, 2022)
Amount students, administrators, and supervisors Theory learning at Pondok boarding school Ma'hadut tholabah That's enough leaky many with management still manually create cottage this experience various obstacles moment To do management, for example cause difficulty for checking students who are still active as well as those who have become alumni. Study this aim for avoid happening errors that arise consequence data recording, realizing something system information management cottage web-based boarding school in which covers aspects service so that could give information needed Cottage Boarding school Ma'hadut tholabah. Study this is study with WDLC method with the stages is analysis, determination specification, site structure and design, development, testing, marketing, and maintenance. Whereas for researcher data collection use method interviews , observations, and literature. On development system information management this researcher using a web server with using MySQL and PHP. MySQL and PHP are used for make system database management that can make it easy system data collection management by computerized. Research results this produce a design system information management Cottage Boarding school Ma'hadut Tulabah who can simplify the management process data collection so that data collection carried out no only manually but can stored in an application program that can accessed by managing admin Cottage Boarding school Ma'hadut tholabah